2015
DOI: 10.1186/s12952-015-0037-5
|View full text |Cite
|
Sign up to set email alerts
|

Early objective response may not be a prognostic factor of survival for patients with metastatic urothelial carcinoma: from a retrospective analysis of a cohort of 113 patients

Abstract: BackgroundThis study aims to better define prognostic factors for patients with metastatic urothelial carcinoma (mUC), and to identify patients who will benefit from first-line cisplatin-based chemotherapy. We test the hypothesis that early objective response (EOR), defined as the occurrence of an objective response following 2 or 3 courses of chemotherapy, could be a prognostic factor for overall survival (OS) and thus be used to guide treatment decisions. Data from 113 patients with evaluable mUC receiving f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…A retrospective analysis of first-line chemotherapy for UC concluded that early response may not predict OS. 23 However, in studies of second-line avelumab in patients with other cancers (metastatic Merkel cell carcinoma or unresectable mesothelioma), objective response achieved within 2–3 months was associated with longer OS compared with patients without an early response. 24 25 …”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of first-line chemotherapy for UC concluded that early response may not predict OS. 23 However, in studies of second-line avelumab in patients with other cancers (metastatic Merkel cell carcinoma or unresectable mesothelioma), objective response achieved within 2–3 months was associated with longer OS compared with patients without an early response. 24 25 …”
Section: Introductionmentioning
confidence: 99%